Synthesis and characterization iron oxide carbon nanotubes nanocomposite by laser ablation for anti-microbial applications - Al-Salih, Moatasem; Samsudin, Syakirah; Arshad, Siti Suri (SpringerOpen, 2021)
Background: Environmental contamination by microbes is a major public health concern. A damp environment is one of the potential sources for microbe proliferation. Smart synthesis nanocatalytic coatings on surfaces, food, and material from different pathogen bacteria can inhibit using the Fe3O4/CNTs as anti-microbial growth can effectively curb this growing threat. In this present work, the anti-microbial efficacy of synthesis of a compound nanoparticle-containing iron oxide-multi-walled carbon nanotube was combined by laser ablation PLAL and explored the anti-bacterial action of colloidal solution of Fe3O4/CNTs NPs that was evaluated against bacteria which is classified as gram-negative (Escherichia coli (E. coli), Klebsiella pneumonia (K. pneumonia), and also that is identified as gram-positive (Streptococcus pyogenes (S .pyogenes) and Staphylococcus aureus (S. aureus) under visible light irradiation. Results: Doping of a minute fraction of iron(III) salt (0.5 mol%) in a volatile solvent (ethanol) was carried out via the sol-gel technique. Fe3O4 was further calcined at various temperatures (in the range of 500–700 °C) to evaluate the thermal stability of the Fe3O4 nanoporous oxidizer nanoparticles. The physicochemical properties of the samples were characterized through X-ray diffraction (XRD), atomic force microscopy (AFM), attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), and UV–Visible spectroscopy techniques. XRD results revealed that the nanoparticles framework of Fe3O4 was maintained well up to 650 °C by the Fe dopant. UV–Vis results suggested that absorption property of combination Fe3O4/CNTs nanopowder by PLAL was enhanced and the band gap is reduced into 2.0 eV. Conclusions: Density functional theory (DFT) studies emphasize the introduction of Fe+ and Fe2+ ions by replacing other ions in the CNT lattice, therefore creating oxygen vacancies. These further promoted anti-microbial efficiency. A significantly high bacterial inactivation that indicates results was evaluated and that the mean estimations of restraint were determined from triple assessment in every appraisal at 400 ml which represent the best anti-bacterial action against gram-positive and gram-negative microbes.